Suplemen kombucha dan kayu manis untuk menghasilkan daging broiler kaya antioksidan dan rendah kolesterol - Laili Fitria Zulfa; Sunarno Sunarno; Salsabila Alifah; Salindri Prawitasari (Jurnal Biologi Tropika, 2019)
Quality and healthy meat is the goal of broiler cultivation. One way to get quality, safe broiler meat is by giving kombucha tea and cinnamon flour supplements in a diet that can lower cholesterol and increase the antioxidant content of meat. This study aims to analyze the cholesterol and antioxidant content of broiler (femoris and  pectoralis major muscles) after the supplementation of kombucha tea and or cinnamon flour in feed. This study uses a completely randomized design consisting of 5 treatments with      4 replications. The treatment in this study included P0: control, without being given kombucha tea and cinnamon flour, P1: 5% cinnamon flour; P2, P3, and P4 respectively are 100% kombucha tea and 5% cinnamon flour with a ratio (3: 1), (1: 1), and (1: 3). The variables measured were total antioxidant and cholesterol levels in the femoral and pectoral major muscles. The research data were analyzed by ANOVA followed by Duncan Test with a confidence level of 95%. The results showed that kombucha tea and cinnamon flour supplements significantly affected antioxidant levels and total cholesterol in broiler meat. The conclusion of this study is that 100% kombucha tea with 5% cinnamon with a ratio (3: 1) and (1: 1) gives the most optimal influence on increasing antioxidant levels and decreasing cholesterol levels in femoral muscle and major pectotalis in broilers.